Explorations of Chinese Theoretical and Applied Linguistics - Chen, Dongyan; Bell, Daniel; Chen, Dongyan; Bell, Daniel (Cambridge Scholars Publishing, 2020)
This volume explores the implications of Chinese for linguistic theory building and for the field of second language acquisition. Bringing together selected papers from the first International Symposium on Chinese Theoretical and Applied Linguistics, it sheds light upon under-documented topics in a variety of areas within theoretical and applied research. The topics covered here include competing approaches within optimality theory to phonological opacity, formal solutions to puzzles in Shanghainese morphosyntax, and different approaches to polarity items and presentational sentences in Chines.